Hemoglobin J-Auckland: a clinically silent low oxygen affinity variant presenting with persistent asymptomatic hypoxemia at high altitude - Ali Alsuheel Asseri; Ibrahim Tawhari; Afaf Haif Qahtani; Ibrahim A. Asiri; Husain Alkhaldy (Hematology)
Background Inherited hemoglobin disorders are common in clinical practice. While qualitative (i.e. sickle cell disease) and quantitative (thalassemia) hemoglobinopathies are usually diagnosed clinically and confirmed through simple laboratory assessments, hemoglobin variants with altered oxygen affinity often go undetected due to their typically silent clinical presentation. Hemoglobin (Hb) J-Auckland, a low oxygen affinity hemoglobin variant first described in 1987 in Auckland, New Zealand, is one such silent disorder.Case presentation We report for the first time a clinically evident case of previously undiagnosed Hb J-Auckland in an 8-year-old girl who presented with unexplained hypoxemia at high altitude. Her oxygen level was corrected with supplemental oxygen and when assessed at low altitude. A brief discussion of the diagnostic approach and clinical implications is provided.Conclusion Standard hemoglobin analysis is essential for the evaluation of suspected altered affinity hemoglobinopathy, and genetic testing is often required for definitive diagnosis. Early recognition and diagnosis of these variants can prevent mismanagement and improve patient outcomes.